Genome-wide RNAi screening identifies host restriction factors critical for in vivo AAV transduction - Mano, Miguel (Proc Natl Acad Sci U S A, 2015)
Viral vectors based on the adeno-associated virus (AAV) hold great promise for in vivo gene transfer; several unknowns, however, still limit the vectors’ broader and more efficient application. Here, we report the results of a high-throughput, whole-genome siRNA screening aimed at identifying cellular factors regulating AAV transduction. We identified 1,483 genes affecting vector efficiency more than 4-fold and up to 50-fold, either negatively or positively. Most of these factors have not previously been associated to AAV infection. The most effective siRNAs were independent from the virus serotype or analyzed cell type and were equally evident for single-stranded and self-complementary AAV vectors. A common characteristic of the most effective siRNAs was the induction of cellular DNA damage and activation of a cell cycle checkpoint. This information can be exploited for the development of more efficient AAV-based gene delivery procedures. Administration of the most effective siRNAs identified by the screening to the liver significantly improved in vivo AAV transduction efficiency.